Pelatihan dalam Penemuan Novelty pada Penulisan Artikel Ilmiah Nasional Bereputasi Sinta - Setiawan, Hendy; Choirunnisa (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This paper aims to describe the results of novelty exploration training in reputable article writing for novice lecturers at Selamat Sri Batang University. This activity was facilitated by the Quality Assurance Institute and the Institute for Research and Community Service of the university. As is known, the issue of improving the quality of writing for lecturers is an absolute requirement in determining the quality of educational personnel. Every lecturer is required to be able to develop and possess good writing skills. This is in line with one of the pillars of the Tridharma of Higher Education, namely the field of research. Therefore, the presence of new lecturers really needs training so that in the future they have writing skills and are able to make real contributions through research work. This service method uses a training program method, where novice lecturers are given training while increasing literacy in developing writing ideas, especially in penetrating reputable national journals. The issue of novelty in writing is the focus of this training so that they have increased capacity in writing scientific papers. Th is activity was attended by 46 novice lecturers with facilitation from the LPM and LPPM Teams. The results show that novice lecturers still do not fully understand how to explore novelty in scientific writing. They consider exploring novelty to be a challenge to date. However, after the training, novice lecturers began to realize the importance of novelty and how to find it in presenting scientific work. Furthermore, most participants considered this activity to be able to foster a spirit of writing, enabling them to publish articles in reputable national journals at a certain level, which is crucial for future functional position advancement.